National Trends in Statin Use among the United States Nursing Home Population (2011 – 2016) - Mack, Deborah S. (Drugs Aging, 2021)
BACKGROUND: Little is known about trends in statin use in United States (US) nursing homes. OBJECTIVES: To describe national trends in statin use in nursing homes and evaluate the impact of the introduction of generic statins, safety warnings, and guideline recommendations on statin use. METHODS: This study employed a repeated cross-sectional prevalence design to evaluate monthly statin use in long-stay US nursing home residents enrolled in Medicare fee-for-service using the Minimum Data Set 3.0 and Medicare Part D claims between April 2011– December 2016. Stratified by age in years (65–75, ≥76), analyses estimated trends and level changes with 95% confidence intervals (CI) following statin-related events (the availability of generic statins, American Heart Association/American College of Cardiology guideline updates, and US Food and Drug Administration safety warnings) through segmented regression models corrected for autocorrelation. RESULTS: Statin use increased from April 2011 to December 2016 (65–75 years: 38.6% to 43.3%; ≥76 years: 26.5% to 30.0%), as did high intensity statin use (65–75 years: 4.8% to 9.5%; ≥76 years: 2.3% to 4.5%). The introduction of generic statins yielded little impact on prevalence of statins in nursing home residents. Positive trend changes in high intensity statin use occurred following national guideline updates in December 2011 (65 to 75 years: β = 0.16; 95% CI: 0.09 to 0.22; ≥76 years: β = 0.09; 95% CI: 0.06 to 0.12) and November 2013 (65 to 75 years: β = 0.11; 95% CI: 0.09 to 0.13; ≥76 years: β = 0.04; 95% CI: 0.03 to 0.05). There were negative trend changes for any statin use concurrent with FDA statin safety warnings in March 2012 among both age groups (65–75 years: β trend change=−0.06; 95% CI: −0.10 to −0.02; ≥76 years: β trend change= −0.05; 95% CI: −0.08 to −0.01). The publication of a statin deprescribing trial results yielded a decrease in any statin use among the ≥76 years age group (β level change= −0.25, 95% CI: −0.48 to −0.09; β trend change= −0.03, 95% CI: −0.04 to −0.01) with both age groups observing a positive trend change with high intensity statins (65 to 75 year age group: β = 0.11; 95% CI: 0.02 to 0.21; ≥76 years age group: β = 0.05; 95% CI: 0.01 to 0.09). CONCLUSION: Overall, statin use in US nursing homes increased from 2011 to 2016. Guidelines and statin-related events appeared to impact use in the nursing home setting. As such, statin guidelines and messaging should provide special consideration for nursing home populations, who may have more risk than benefit from statin pharmacotherapy.